Transformational leadership of the administrators influence on the success of the use of information technology. In Thawi Watthana District Office Bangkok. - Phothikul, Anan (Journal of Management Science Nakhon Pathom Rajabhat University, 2019)
The objectives of this research are following; To study the transformational leadership of the administrators that influence the success of using information technology in Thawi Watthana District Office. Bangkok In this research, the researcher uses the quantitative data methodology by using a questionnaire to collect data from the population of 128 ordinary Bangkok civil servants and 100 samples, calculated from the Taro Yamane formula and using Cluster random sampling in order to obtain appropriate samples for data collection Data analysis The researcher processed using the software package for social science research. And use inferential statistics to test hypotheses, including multiple regression analysis. Hypothesis test results It was found that the transformational leadership of the administrators as a whole had an influence on the success of using information technology in Thawi Watthana District Office. Bangkok The regression equation can be written as follows: The success of using information technology = = 0.962 + 0.259 (Corporate orientation to the future) + 0.310 (Good leaders must be good role models for others) + 0.200 (Organizational orientation to achieve desired direction) as well as the overall transformational leadership of the administrators can predict the success of using technology. 53.90 percent of the information. The said percentage shows that this model has moderate reliability. In addition, the overall transformational leadership of the administrators also influenced the prediction of the success of using information technology by 77.10 percent. Article history : Received 2 November 2019 Revised 21 November 2019 Accepted 28 November 2019 SIMILARITY INDEX = 2.75